El enfoque sistémico en terapia familiar - Zevallos Vega, Roxana (1993)
The author reviews sorne aspects of the onset of Family Therapy. The different stages are described, emphasizing the work of authors such as Hoffrnan, Minuchin, Maturana, among others. The beginning of Family Therapy in Peru is outlined and professional groups working in the field are mnentioned